2002
DOI: 10.1128/aem.68.9.4377-4382.2002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tropolone on Poria placenta Wood Degradation

Abstract: Fenton reactions are believed to play important roles in wood degradation by brown rot fungi. In this context, the effect of tropolone (2-hydroxycyclohepta-2,4,6-trienone), a metal chelator, on wood degradation by Poria placenta was investigated. Tropolone (50 M) strongly inhibits fungal growth on malt agar, but this inhibition could be relieved by adding iron salts. With an experimental system containing two separate parts, one supplemented with tropolone (100 M) and the other not, it was shown that the fungu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Tropolone is a chelating agent with a strong affinity for ferric ions (12,17). Tropolone was placed into holes (0.1, 0.2, 0.5, 1.0, 1.5, and 2.0 mg/hole) in PDA plates seeded with Botrytis conidia, which resulted in growth inhibition similar to that observed with the Metschnikowia isolates (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tropolone is a chelating agent with a strong affinity for ferric ions (12,17). Tropolone was placed into holes (0.1, 0.2, 0.5, 1.0, 1.5, and 2.0 mg/hole) in PDA plates seeded with Botrytis conidia, which resulted in growth inhibition similar to that observed with the Metschnikowia isolates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of strains to iron depletion was tested with tropolone (2-hydroxycyclohepta-2,4,6-trienone; T7387; Sigma-Aldrich Co., St. Louis, Mo. ), a chelating agent with a strong affinity for ferric ions (12,17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We report here the structure-activity relationship of tropolones available in the National Cancer Institute compound repository on HIV integrase activities. Tropolone derivatives are present in cupressaceous trees from genus Thuja and are probably responsible for resistance of fungal and insect attack on the heartwood (Baya et al, 2001;Diouf et al, 2002;Lim et al, 2005). Our experiments demonstrate the ability of the monomer 7-hydroxytropolones (␣-hydroxytropolones) to preferentially inhibit the ST reaction by interfering with the enzyme catalytic site.…”
mentioning
confidence: 79%
“…Diouf et al studied the influence of tropolone on the wood degradation and they found weak antioxidative and radical scavenging properties. Moreover, they also showed tropolone can be used as novel environmentally benign preservative systems [2]. Kadoma and co-workers studied the kinetic radical scavenging activity (RSA) of tropolone by induction period method and found very weak antioxidant properties [3].…”
Section: Introductionmentioning
confidence: 99%